New evidences for old biomarkers: Effects of several xenobiotics on EROD and AChE activities in Zebra mussel ( Dreissena polymorpha) - Binelli, A.; Ricciardi, F.; Riva, C.; Provini, A. (Chemosphere (Oxford), 2006)
The biomarker approach is widely used both in vertebrates and invertebrates for environmental biomonitoring, because it can supply an integrated response for multi-xenobiotics contamination. However, the use of biomarkers requires the identification of every possible variation that can influence the biochemical response, because ecosystems are generally subject to a mixture of pollutants, which can create additive, opposite or competitive effects. In recent years, there has been considerable interest in the use of biomarkers within marine bivalves, while very few data are available for freshwater molluscs. The aim of this research was to investigate changes on EROD and AChE activities in the freshwater bivalve Zebra mussel ( Dreissena polymorpha) exposed to different pollutants (Arochlor 1260, CB 153 and 126, pp’DDT, chlorpyrifos, carbaryl) at laboratory conditions, in order to standardize the analytical procedures and to highlight eventual interferences on enzyme activities. Chemical concentrations in the mussel soft tissues were analyzed by GC/MS-MS. Main results showed a significant induction of EROD activity when mussels were exposed to 100 ng/l of PCB mixture of Arochlor 1260 and dioxin-like CB 126, but this congener showed also a clear competitive inhibition after 48 h of exposure. Surprisingly, pp’DDT determined a significant decrease of basal EROD activity after only 24 h of exposure, even if it was not possible to discriminate between the effect of the parent compound and that of its metabolites (DDD, DDE). We also found an interaction between the organophosphate insecticide chlorpyrifos, which does not directly decrease the AChE activity, and terbutilazine. This herbicide increased the biotransformation of the organophosphate compound to its oxidized metabolite (oxon), a much stronger AChE inhibitor. The possible use of the oxime Pyridine-2-Aldoxime Methochloride (2-PAM) to bring back the catalytic activity to basal levels was also demonstrated.